Human infective endocarditis and septic shock caused by Streptococcus suis serotype 1 - Wei Yang; Chun Yang; Xiaoxiong Lu (BMC Infectious Diseases)
Abstract Streptococcus suis(SS) infection is a zoonotic acute infectious disease, SS infective endocarditis is relatively rare, there is no case report of Streptococcus suis Serotype 1(SS1) causing mitral valve infection.The rapid progression of this patient’s infection and the severe damage to the valve structure differ from the previous understanding of the relatively low virulence of SS1. Early diagnosis and selection of the correct antibiotic treatment according to the drug sensitivity is very important. If the infection causes damage to the structure of the body’s mitral valve, resulting in regurgitation of blood and heart failure, prompt surgical treatment should be performed to improve heart function.